Penerapan Demokrasi Pendidikan pada Pembelajaran Siswa di Sekolah Dasar - Khuzaimah, Khuzaimah; Farid Pribadi (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2022)
Education is the need of everyone in this era. Education from time to time always develops in a better direction, such as the implementation of educational democracy in learning that carries the concept of giving students freedom in expressing opinions, expressing objections, and also having equal opportunities without any distinction in terms of ethnicity, race, and class. This study seeks to determine the application of Educational democracy in the learning process of elementary school students where students are not only used as objects of learning but also become subjects who are involved in discussions during the learning process. This research was conducted by means of a literature study in which looking for references through journals, articles, and websites available on the internet and analyzed using qualitative methods using data analysis techniques through four stages, namely searching